Digital "formats" and "narratives": similarities, differences and conceptual delimitation of some of the most common formats - Rojas-Torrijos, José Luis; Herrera-Damas, Susana (Infonomy, 2024)
This brief essay attempts to establish the main differences between the terms "format" and "narrative" in their application to journalistic innovation. Both concepts have been widely used in recent years in view of the numerous expressive possibilities offered by technological advances. Although on many occasions they have been used interchangeably, each of them has its own entity. In the second part of the text, we will present the keys to some of the main formats that journalism can resort to today.